Analisis Putusan Pengadilan Negeri Muaro Yang Membatalkan Putusan Badan Penyelesaian Sengketa Konsumen Terhadap Perjanjian Pembiayaan (Studi Putusan Nomor: 4/Pdt.Sus-Bpsk/2024/Pn Mrj) - Yunimar , Ananta Fadhilah (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
The Consumer Dispute Settlement Agency (Badan Penyelesaian Sengketa Konsumen/BPSK) is an institution established to protect consumer rights and provide an alternative mechanism for resolving disputes between consumers and business actors. However, in practice, parties often raise objections to BPSK decisions and subsequently file annulment claims before the District Court. This issue is reflected in the Supreme Court Decision of the Republic of Indonesia Number 27 K/Pdt.Sus/2013 dated March 26, 2013, which establishes the legal principle that disputes arising from financing agreements, whether secured by mortgage rights or fiduciary guarantees, are not subject to the Consumer Protection Law and therefore fall outside the authority of BPSK. The research questions addressed in this study are: First, what were the legal considerations of the Muaro District Court judges in annulling the BPSK decision concerning a financing agreement as reflected in Decision Number 4/Pdt.Sus-BPSK/2024/PN Mrj? Second, how can the Muaro District Court decision annulling the BPSK ruling in the same case be analyzed from a legal perspective? This research employs a normative juridical approach by examining legal doctrines, principles, statutory regulations, and court decisions. The data were processed through editing and coding techniques and analyzed qualitatively. The results of the study indicate that the Muaro District Court judges considered the dispute arising from the financing agreement as a case of breach of contract (wanprestasi), which falls under the absolute jurisdiction of the District Court rather than BPSK. Furthermore, the juridical analysis shows that the annulment of the BPSK decision was legally justified and consistent with Supreme Court Regulation (PERMA) Number 1 of 2006, Article 45 paragraph (2) of Law Number 8 of 1999 on Consumer Protection, and Supreme Court jurisprudence regarding the limits of BPSK’s authority. Therefore, it is recommended that BPSK carry out its duties strictly in accordance with applicable regulations, while the public is encouraged to better understand the legal framework governing consumer dispute resolution to ensure legal certainty, justice, and societal welfare.